Benefits of Interventional Telemonitoring on Survival and Unplanned Hospitalization in Patients With Chronic Heart Failure - Galinier, Michel; Itier, Romain; Matta, Anthony; Massot, Montse; Fournier, Pauline; Galtier, Ghislaine; Ayot, Sandrine; Nader, Vanessa; Rene, Max; Lecourt, Laurent; Roncalli, Jerome (Frontiers in Cardiovascular Medicine, 2022)
Aims To assess the effect of interventional specialized telemonitoring (ITM) compared to standard telemonitoring (STM) and standard of care (SC) on preventing all causes of death, cardiovascular mortality and unplanned hospitalization in heart failure (HF) patients. Methods We compared outcomes in three groups of HF patients followed by different modalities: SC, STM and ITM. The telemonitoring was performed by the specialized HF-cardiology staff at Toulouse University Hospital. All patients were followed with the same manner including daily weight monitoring using on-line scales, self-monitoring and reporting symptoms via a device. The difference between groups was in the management of the received alerts. In STM-group, patients were contacted by a member of telemedical center and the main responsibility for patient's therapy was taken by their primary care physicians while in the ITM-group, a cardiologist intervenes immediately in case of alerts for diuretic dose adjustment or escalation therapy or programmed hospitalization if necessary. Outcomes were compared between the three study groups and Kaplan-Meier analysis was performed. Results Four hundred fourteen HF-patients derived from two French cohorts (OSICAT and ETAPES) were included in this study and subsequently enrolled in the following three groups: ITM-group (n = 220), STM-group (n = 99), and SC-group (n = 95). During the mean follow-up period of 341 days, there were significantly fewer primary endpoints like unplanned hospitalization (13.6 vs. 34.3 vs. 36.8%, p < 0.05), all-causes of death (4.5 vs. 20.2 vs. 16.8%, p < 0.05) and cardiovascular mortality (3.2 vs. 15.2 vs. 8.4%, p < 0.05) in the ITM-group. The multivariable logistic regression revealed a significant negative association between the ITM and unplanned hospitalization [OR = 0.303 95% CI (0.165–0.555), p < 0.001) and all-causes of death [OR = 0.255 95% CI (0.103–0.628), p = 0.003], respectively. Kaplan Meier and log rank test showed significant difference in median event-free survival in favor of ITM-group. Conclusions In the ITM follow-up HF group, delivered by a cardiology team, the rate of unplanned hospitalization and all-causes of death are lower than SC or STM.